PREVALENCE OF SOME INTESTINAL PARASITIC INFECTIONS IN RELATION TO BODY MASS INDEX OF CHILDREN RESIDENT IN ORPHANAGES IN ANAMBRA STATE, NIGERIA - B. O., Oluboyo; I. B., Enweani; I. M., Ekejindu; A. O., Oluboyo (European Scientific Journal, ESJ, 2014)
There is paucity of information on the prevalence of intestinal parasitic infections in orphanage homes in Anambra State, Nigeria. This study investigated the prevalence of some intestinal parasitic infections in relation to Body Mass Index (BMI) of children resident in orphanages situated in Anambra State. A total of 272 subjects comprising 172 orphans and 100 children in family setting (control) were investigated for intestinal parasites using formol-ether concentration method. Underweight, overweight and obesity were determined from BMI using the International Obesity Task Force cut-off points. Prevalence of 23.3%, 5.8%, 4.7% and 1.2% were observed for Ascaris lumbricoides, Necator americanus/Ancylostoma duodenale, and Entamoeba histolytica/dispar infections respectively. Prevalence of 12.8% and 9.0% were observed in children of orphanages and children living in their families respectively (P = 0.045, P < 0.05). The mean BMI of children living with their families was significantly higher than that of children in the orphanages (P = 0.000, P < 0.05). However, this was not related to parasitic infestation. It may be related to the level of care giving to the children in the orphanages. Underweight children were 8.1% and 0% in children of orphanages and families respectively while overweight children were 3.5% and 8.0% respectively. Children in family setting seem to thrive better than those in orphanages.